2016
DOI: 10.1371/journal.pone.0162762
|View full text |Cite
|
Sign up to set email alerts
|

The Activation Effects of Low Level Isopropyl Alcohol Exposure on Arterial Blood Pressures Are Associated with Decreased 5-Hydroxyindole Acetic Acid in Urine

Abstract: PurposesThe objectives of this paper are to study the impact of low level isopropyl alcohol exposure on blood pressure and to explore its potential mechanism.MethodsThis cross-sectional study was based on a prospective occupational cohort in south China, which focusing on occupational risk factors related cardiovascular health problems. A total of 283 participants (200 low isopropyl alcohol exposed workers and 83 controls) was finally enrolled in this study. Linear regression models were used to analyze the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…11 Isopropanol is being widely used in various applications such as lubricants, solvents, cosmetics, electronic industries for cleaning of printed circuit boards, pharmaceutical industries, household chemicals, and also in automotive eld as a petroleum additive. [12][13][14] However, exposure to isopropanol is very harmful to human health. Dizziness, severe vomiting, irritation of eyes, nose, throat, and mouth are the common symptoms that are being observed while exposing to low concentrated isopropanol (below 400 ppm).…”
Section: Introductionmentioning
confidence: 99%
“…11 Isopropanol is being widely used in various applications such as lubricants, solvents, cosmetics, electronic industries for cleaning of printed circuit boards, pharmaceutical industries, household chemicals, and also in automotive eld as a petroleum additive. [12][13][14] However, exposure to isopropanol is very harmful to human health. Dizziness, severe vomiting, irritation of eyes, nose, throat, and mouth are the common symptoms that are being observed while exposing to low concentrated isopropanol (below 400 ppm).…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of alcohol can be life threatening if no measures are taken properly. Alcohol such as isopropyl alcohol (isopropanol) is a clear, colorless, and flammable organic solvents [7]. There has been a report that isopropyl alcohol (IPA) exposure mainly affects the nervous system, but it may also lead to reproductive development problems [8].…”
Section: Photonic Sensorsmentioning
confidence: 99%
“…But low-level isopropanol exposure-caused potential health hazards are often ignored. Our research team found that even low-level isopropanol exposure could cause 5-hydroxy indole acetic acid (5-HIAA) decreasing, correlated with increased blood pressure [ 9 ]. Although the exact mechanism of action of isopropanol has not been fully elucidated, recent studies have suggested that isopropanol affects liver metabolic enzyme activity [ 10 ] and promotes the genotoxicity of other substances [ 11 ].…”
Section: Introductionmentioning
confidence: 99%